Pengaruh Penerapan Model Pembelajaran Connecting Organizing Reflecting Extending Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 13 Padang - RISA MELSI BONI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Oneeof the1cognitiveeabilitiessthat is expectedtto be possesseddby every students in learning mathematics  is  the  understanding  of  mathematical  concepts.  However,  the  fact  is  understanding  of mathematical  concepts  ofiistudents  in  grade  VIII3SMPN  13  Padang  is  still  low,  so  it  needs  to  be improved. One of the learning models to improve the understanding of mathematical concepts of students is  the  CORE  learning8model.  The  type  of  this  research  are  the  combination  of  quasy-experiment  and descriptive research with theiiStatic Group Design. Based3on data analysis the0resultrofoquiz it can be conclude  that  the  understanding  of  mathematicalcconcepts  among  using  CORE    model tendencyiiincreasing.  Based  on  the  resultsiiof  data  analysis  using  t  test,  it  can  be  concluded  that theuunderstanding  of  mathematical  concepts  of  students  that  study  by1CORE  learning  modellis  better than understanding of mathematical concepts of students that study by direct learning. Keywords – CORE iiLearningiiModel,iiUnderstandingiiof MathematicaliiConcept, Direct learning.